Connotations of Sanxingdui as a Theocratic Civilization - DUAN Yu (Frontiers of history in China, 2022)
The discoveries of the Sanxingdui culture, including the magnificent ancient city, the splendid bronze ware clusters, the original characters, the great art, the grand ritual center, and other material civilizational elements, contain the essential and structural characteristics of the institutional civilization and spiritual civilization of the ancient Shu civilization and reflect the theocratic regime of the Sanxingdui civilization. As a symbol to command the ethnic groups from southwestern China, the ivory sacrificial ritual in the Sanxingdui culture played a significant role. The discoveries of silk residues and silk proteins at Sanxingdui provide important evidence for the historical records of the Shushan Clan and Cancong Clan, as well as the splendid clothing of the Large Standing Bronze Figure at Sanxingdui, and even the relationship between the Sanxingdui culture and the Southern Silk Road.